Nursing in adherence to treatment of tuberculosis and health technologies in the context of primary care - Rayrla Cristina de Abreu Temoteo; Jovanka Bittencourt Leite de Carvalho; Ana Luisa Brandão de Carvalho Lira; Maria Alzete de Lima; Yanna Gomes de Sousa (Escola Anna Nery)
Abstract Objective: To describe and analyze the relationships between adherence to tuberculosis treatment and health technologies in the context of nursing action in Primary Care. Method: Contextual reflection, using the theoretical reference of Hinds, Chaves and Cypress. Results: They were categorized according to the conceptual perspective of each context, in an immediate, specific, general and metacontext, respectively: nursing actions in Primary Care and adherence to treatment of tuberculosis; nurses' performance through personal and environmental factors, health technologies and adherence to treatment; influence of nurses' beliefs about adherence to treatment and overall health status, and use of health technologies and shared views of patients and nurses on adherence to treatment as a responsibility for preventive action. Conclusion and Implications for practice: Adherence to the treatment of tuberculosis is directly linked to the substantial performance of the nurse, which presents potentialities to contribute to greater articulation between actions necessary to the success of the treatment, reducing the weaknesses in its operationalization. The technologies in the context of nursing action can favor praxis, especially in the incentive to join, and can subsidize new strategies appropriate to the reality of services.